Jamaica. Annual report 2008 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This report details the results of the contributions made by the Jamaica office in 2008 in its four strategic areas of cooperation and in support of the Government's current agenda to modernize agriculture, build capacity and ensure the nation's food security. It highlights the partnerships formed to facilitate the various interventions, examines the major developments that characterised the local agricultural sector for the review period and identifies opportunities for future technical cooperation in Jamaica.